Microevolution Analysis of Bacillus coahuilensis Unveils Differences in Phosphorus Acquisition Strategies and Their Regulation - Gómez-Lunar, Zulema; Hernández-González, Ismael; Rodríguez-Torres, María-Dolores; Souza, Valeria; Olmedo-Álvarez, Gabriela (Frontiers in Microbiology, 2016)
Bacterial genomes undergo numerous events of gene losses and gains that generate genome variability among strains of the same species (microevolution). Our aim was to compare the genomes and relevant phenotypes of three Bacillus coahuilensis strains from two oligotrophic hydrological systems in the Cuatro Ciénegas Basin (México), to unveil the environmental challenges that this species cope with, and the microevolutionary differences in these genotypes. Since the strains were isolated from a low P environment, we placed emphasis on the search of different phosphorus acquisition strategies. The three B. coahuilensis strains exhibited similar numbers of coding DNA sequences, of which 82% (2, 893) constituted the core genome, and 18% corresponded to accessory genes. Most of the genes in this last group were associated with mobile genetic elements or were annotated as hypothetical proteins. Ten percent of the pangenome consisted of strain-specific genes. Alignment of the three B. coahuilensis genomes indicated a high level of synteny and revealed the presence of several genomic islands. Unexpectedly, one of these islands contained genes that encode the 2-keto-3-deoxymannooctulosonic acid (Kdo) biosynthesis enzymes, a feature associated to cell walls of Gram-negative bacteria. Some microevolutionary changes were clearly associated with mobile genetic elements. Our analysis revealed inconsistencies between phenotype and genotype, which we suggest result from the impossibility to map regulatory features to genome analysis. Experimental results revealed variability in the types and numbers of auxotrophies between the strains that could not consistently be explained by in silico metabolic models. Several intraspecific differences in preferences for carbohydrate and phosphorus utilization were observed. Regarding phosphorus recycling, scavenging, and storage, variations were found between the three genomes. The three strains exhibited differences regarding alkaline phosphatase suggesting that in addition to gene gain and loss; regulation adjustment of gene expression also has contributed to the intraspecific diversity of B. coahuilensis.